Edukasi Literasi Bahasa Digital Untuk Mewujudkan Etika Komunikasi Digital Yang Bijak Bagi Siswa SMK Nurul Huda Sagalaherang - Putri Yulia Handini; Firda Putri Aulia; Pipit Fitriyani Rahayu Ningsih; Gilang Herdiana Rahmat; Desti Kusmayanti; Annisa Mazda Firdaus; Achmad Vindo Galaresa (Inisiatif : Jurnal Dedikasi Pengabdian Masyarakat, 2026)
The rapid development of digital technology has not been well-balanced by an understanding of communication ethics among adolescents, thereby triggering the widespread dissemination of hoaxes and cyberbullying. This community engagement program aims to enhance students' digital language literacy at SMK Nurul Huda Sagalaherang to foster wise and safe communication in the digital sphere. The subjects of this activity consisted of 12 students divided into three small discussion groups. The program applied the Participatory Action Research (PAR) approach through classical education methods, group discussions, and case studies of actual news utilizing PowerPoint media. The results demonstrated that this participatory approach successfully stimulated students' active engagement in analyzing cyber issues. The program's outcomes proved a significant increase in students' understanding regarding the importance of linguistic politeness, critical thinking in filtering information, and cultivating ethical responsibilities on social media. This PAR-based educational model can be replicated as a preventive school measure to mitigate cyberbullying.